Ultrasound response to tofacitinib in patients with rheumatoid arthritis: Data from a multicenter 24 weeks prospective study - Germanò, Giuseppe; Macchioni, Pierluigi; Maranini, Beatrice; Ciancio, Giovanni; Bonazza, Sara; Govoni, Marcello; Salvarani, Carlo (Frontiers in Medicine, 2022)
Background: Treatment of rheumatoid arthritis (RA) should aim at full remission. Ultrasonography (US) might have an added value to clinical examination in assessing disease activity of RA. In this study we evaluated the ultrasound response to Tofacitinib (TOF), next to clinical and laboratory response, in RA patients treated with tofacitinib (TOF). Methods: In this observational multicenter study, patients received TOF 5 mg twice daily, with or without the contemporary use of methotrexate or other conventional DMARD, for 24 weeks. All patients underwent clinical, laboratory and US examinations of 40 sites among joints and tendons. Sonographers were blinded to clinical and laboratory parameters. Data were assessed at baseline, week 2, 4, 8, 12 and 24. For each patient we used two US joint scores (Gray Scale –GS–and power Doppler –PD– score), a 0-3 semi-quantitative scale for each joint and the EULAR-OMERACT US scoring system (combined GS and PD graded from 0 to 3). Besides, we calculated a tenosynovitis scores (GS and PD) according to the OMERACT score. Results: 52 RA patients completed the 6 months period study: mean disease duration 9.97 + 8.75 years , baseline DAS28-CRP 4.9 + 1.2, HAQ 1.4 + 0.7, C-reactive protein (CRP 2.25 + 3.11 mg/dl). Baseline joint (GS, PD and combined-US) and tendon US scores (GS and PD) were 23.5 + 18.4, 22.7 + 19.3, 25.7 + 20.6, 10.5 + 11.4 and 11.0 + 12.0, respectively. US joint and tendon scores significantly reduced as early as T1 (week 2) examination as well as at week 4, 12 and 24, as compared to baseline values (p < 0.001 for all comparisons). Improvement of joint US scores (GS, PD and US-combined) correlated at T4 examination, with the reduction of serum CRP levels (rho 0.418, p = 0.036, rho 0.495, p=0.004 and rho 0.454, p=0.009, respectively). We did not find any correlation between the variations of DAS28-CRP and any US scores at any visits. Conclusion: These results provide evidence that TOF treatment leads to early (2 weeks) and persistent reduction of US signs of inflammation both at tendon and joint level comparable to clinical improvement.